Rural Economic Development: Whaling and Mink Farming in Newfoundland, 1935-1971 - Dickinson, Anthony; Sanger, Chesley (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2024)
Small-scale mink farming began in Newfoundland in 1935, but was expanded after the Second World War to further rural economic development. Breeders were attracted from Canada and the USA by the government’s offer of low-cost meat from long-finned pilot (pothead) and minke whales, together with shipping and establishment incentives. As a consequence, the pothead stock was overexploited, which, with declining markets, ended whaling-supported mink farming in 1971. It would, in any case, have ceased the following year after a ban on non-Indigenous whaling was imposed by the Canadian government.